LINGUISTIC AND PRAGMATIC POTENTIAL OF ADVERTISING NAMES (AS EXEMPLIFIED BY NAMES OF COSMETIC GOODS) - Marina Yu. Krinitskaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2020)
The article focuses on specifics of advertising names given to cosmetic products. The purpose of work is to study the efficiency of the considered linguistic units influence on the addressee’s perception, and to analyze the information value of these nominations. The associative experiment was carried out among Russian women within the framework of the study. The word trademarks of cosmetic products formed from toponyms and adjectival and genitive phrases were the stimulus material for the experiment. As a result, it was found out that the majority of advertising names for hair dyes, lipsticks, and lip gloss should be recognized ineffective from the point of view of informative value, because the ideas about color are noticeably different from the objective information which manufacturer or consumers demonstrate. The results of the study are of interest to advertising experts, marketing specialists and linguists, as well as the presented information can be useful in translation practice and creation of new advertising names. Conclusions are drawn that effectively operating advertising name is such a name that should be easily remembered, cause positive associations, be understandable to consumers, have emotional and evaluative connotation, which can appeal to the addressee’s emotions, values.